New in treatment of hyperactive bladder with urge urinary incontinence in women - A. I. Neimark; M. V. Razdorskaya; I. V. Snegiryov (Бюллетень сибирской медицины, 2012)
The combination of α1 adrenoceptor blocking agent and phosphodiesterase  inhibitor of 5th type is efficient in treatment of women with hyperactive bladder and urge urinary incontinence, which was proved by the studies of urodynamic and microcirculation of mucous coat of bladder.